Predictive Value of Cerebrospinal Fluid Lactate Level for the Diagnosis of Bacterial Meningitis following Cranial Surgery - Kharel, Ashok; Sedain, Gopal; Shilpakar, Sushil krishna; Sharma, Mohan Raj (Nepal Journal of Neuroscience, 2021)
Background:To distinguish post-neurosurgical bacterial meningitis (PNBM) from aseptic meningitis is difficult. Inflammatory and biochemical cerebrospinal fluid (CSF) changes mimic those classically observed after CNS surgery. CSF lactate assay has therefore been proposed as a useful PNBM marker.Objective:To determine the value of cerebrospinal fluid (CSF) lactate level for the identification of bacterial meningitis following cranial surgery.Methods:Between January 2016 and December 2016, a prospective clinical study was done in Department of Neurosurgery, in which all patients with clinical suspicion of PNBM were enrolled. Patients with clinical suspicion of bacterial meningitis BM were categorized, according to preset criteria, into 3 groups: (1) proven BM; (2) presumed BM, and (3) nonbacterial meningeal syndrome. CSF markers were plotted in a receiver operating curve (ROC) to evaluate their diagnostic accuracy.Results:The study included 70 patients. We obtained 65 CSF samples from patients with clinical suspicion of BM by CSF analysis. 20 corresponded to proven BM, 7 to probable BM and 38 to excluded BM. Mean lactate in CSF was: 8.4 ±3.0 mmol /l for proven BM, 4.8 ± 0.99 mmol /l for probable BM and 2.08 ± 0.822 mmol/l for excluded BM (P < .001).Conclusion: CSF lactate level has good predictive value to distinguish BM from aseptic meningitis with sensitivity of 90% and specificity: 87% at cut-off value: 4.0 mmol/l.